Corporate Social Responsibility Disclosure and Cost Equity Capital in Industrial Product Industry - Mohd Razali, Mohd Waliuddin; Wong, Yik Fui; Ahmad Hajazi, Mohd Uzairi (2017)
Nowadays, corporate social responsibility (CSR) disclosure is becoming increasingly popular and being discussed by all walks of life. Through a strategic approach to CSR, companies are able to boost its competitiveness while gaining other benefits from risk management, reducing cost, and better access to capital, innovation and development. The main objective of the study is to investigate the CSR disclosure by companies listed under industrial product industry toward cost of equity capital. The CSR disclosure score is measured the extent of CSR disclose in the annual report. A total of 59 samples of annual reports listed companies for the period of 2012 to 2014 were obtained and examined. After controlling such as company size, liquidity, and board independence, the regression results showed CSR disclosure, and other control variables such as company size, liquidity, and board independence had negative relationship with cost of equity capital. However, only company size has positive relationship with the cost of equity capital. The results revealed that the CSR disclosure in the annual reports reduces the cost of equity capital by reduce the information asymmetry and reduce companies’ risk. For future research, this paper recommend study being expand using other CSR index and measurement of cost of equity.